(Latihan Dasar Kepemimpinan Taruna) Batalyon Taruna Akademi Maritim Nusantara Banjarmasin - Moch. Nurdin; Kamsariaty; Irnita Rosaria Santi; Hidayati Desy; Juhrani; Prihatin; Irtania; Ahmad Shofi Khairian (Akademi Maritim Nusantara Banjarmasin, 2023)
Abstract Training can also be said as a systematic practice process that is carried out repeatedly, the amount of training load is increasing day by day. Based on the description above, it can be concluded that training is a process of sports activity that is carried out consciously, systematically, gradually and repeatedly, with a relatively long time, to achieve the ultimate goal of an appearance, namely an increase in optimal performance. This activity aims to instill identity as a leader who can be responsible, disciplined and beneficial to those around him. After the material was explained, it was followed by a discussion in the form of questions and answers between the speaker and the participants, namely the Banjarmasin Archipelago Maritime Academy cadets. Discussions are held so that the trainees better understand the material that has been presented. Techniques or stages of implementing community service in basic leadership training for cadet Battalion cadets at the Banjarmasin Archipelago Maritime Academy. The community service program is carried out in the form of training for cadets of the Banjarmasin Archipelago Maritime Academy and the material is in the form of material presentation.